Piano sonata no. 24 in F-sharp major, op. 78, edited by Moscheles - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Moscheles, Ignaz, 1794-1870 (editor):::Contributor:::::::::::: (France; E. Gérard; Paris, 2024)
Piano sonata no. 24 in F-sharp major, op. 78, published by Gérard as for section 3 of the Édition classique des oeuvres spéciales pour piano a deux mains, with pedal markings, fingerings, and Moscheles's metronome markings.